2019
DOI: 10.1111/jce.13876
|View full text |Cite
|
Sign up to set email alerts
|

A left common pulmonary vein: Anatomical variant predicting good outcomes of repeat catheter ablation for atrial fibrillation

Abstract: Introduction A left common pulmonary vein (LCPV) is a common anatomical variant in atrial fibrillation (AF) patients. Whether an LCPV influences outcomes of repeated radiofrequency catheter ablation (RFCA) for AF has not been elucidated. Methods From a prospectively collected database, we enrolled 154 patients who received repeated RFCA for recurrent AF after the initial RFCA (56 ± 9 years, 72% paroxysmal AF, 32 patients with an LCPV, and 122 patients with typical left‐sided pulmonary veins [PVs]). Median post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 28 publications
0
24
0
3
Order By: Relevance
“…To date, studies evaluating the presence of an LCPV affecting ablation success have shown variable results. 5,6,14,15,22 However, these studies were limited by a small sample size, a mixed population of both paroxysmal and persistent AF, and a majority of them employed the RF ablation technique. On reviewing the existing literature, we identified only one small single-center study which exclusively looked at paroxysmal AF patients undergoing CBA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, studies evaluating the presence of an LCPV affecting ablation success have shown variable results. 5,6,14,15,22 However, these studies were limited by a small sample size, a mixed population of both paroxysmal and persistent AF, and a majority of them employed the RF ablation technique. On reviewing the existing literature, we identified only one small single-center study which exclusively looked at paroxysmal AF patients undergoing CBA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies evaluating the presence of an LCPV affecting CBA outcomes have shown variable results. 5,14,15 A number of single-center studies have also assessed the role of PV anatomical indices such as eccentricity index (EI), area of vein (PVA) and ovality index (OI) in relation to CBA outcomes. 12,13,16 However, these studies were limited by a small sample size and the inclusion of a mixed population of both paroxysmal and persistent AF patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared to our study, they included only patients with paroxysmal AF. Another recent study of Xu et al [23] showed that a LCPV was independently associated with better outcomes after repeated RFCA of AF, when compared with typical left-sided PVs. The study also reports that PV reconnection is more frequently identified in cases that present a LCPV anomaly, explaining to some degree the link between this anomaly and the results of repeated ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Според различни проучвания анатомични варианти на белодробния венозен дренаж в ЛП се откриват често и варират в много широки граници -от 19 до 75% [2][3][4][5][6][7][8]. Едновременно възникна и интерес дали вариантната анатомия повлиява по някакъв начин непосредствените и отдалечените резултати от аблацията за ПМ [9][10][11][12][13]. Докладваните резултати са разнопосочни.…”
unclassified
“…According to various studies, anatomical variants of pulmonary venous drainage in the LA are often found and vary in a very wide range -from 19 to 75% [2 -8]. At the same time, there was interest in whether variant anatomy in any way aff ects the acute and remote results of ablation for AF [9][10][11][12][13]. The reported results are inconsistent.…”
mentioning
confidence: 99%